The Effect Of Live Modeling On The Consumption Of Healthy Snacks And Consumption Of Fruit-Vegetables In Students In Samarinda Elementary Schools - Lubis, Bachtiar Safrudin; Pipit Feriani Danial; Burhanto; Shely Salsabila Sari; Nisa Solikha Adiasih (Universitas Muhammadiyah Kalimantan Timur, 2025)
School-age children are a risk group because of their tendency to imitate behavior both at home and outside the home. One thing to pay attention to is the habit of eating and consuming vegetables and fruits. Characteristics of children in imitating the behavior of others as a model in implementing everyday behavior. This study aims to determine the effect of live modeling on vegetable and fruit consumption behavior in students at SDN 020 Samarinda. Pre-experiment research design without control. The population in this study amounted to 57 students. The technique of taking purposive sampling as many as 11 respondents. The instrument used in the study used an observation sheet on vegetable and fruit consumption behavior. The statistical analysis used was the Wilcoxon test. There is an effect of giving live modeling on healthy snacking behavior and consumption of fruit and vegetables (0.009; 0.003 < α 0.05). This means that there is an influence of live modeling on the behavior of snacking on sehan and consumption of vegetables and fruits